Integrating Flood Risk Management into Development Projects: A Conceptual Framework for Resilient Urban Planning - Saad, Mohammad Syamsyul Hairi; Ali, Mohamad Idris; Razi, Putri Zulaiha; Ramli, Noram Irwan; Putra Jaya, Ramadhansyah (Popular Scientist, 2025)
Flood risk is an increasingly critical concern in urban development as the frequency and severity of floods escalate due to climate change and intensified economic activities. Despite extensive studies on flood risk management (FRM), a significant gap persists in practical frameworks that systematically integrate FRM principles across the entire lifecycle of development projects. To address this gap, this study conducted a scoping review of 27 peer-reviewed articles published between 2014 and 2024, retrieved from Scopus, ScienceDirect, and Google Scholar databases. Using a thematic analysis approach, four major themes were identified: (1) the risk–hazard model, (2) risk assessment theory, (3) project lifecycle theory, and (4) risk management theory. These themes were synthesized to develop a unified conceptual framework that embeds FRM throughout project planning, design, implementation, and operation. The proposed framework emphasizes early risk identification, continuous stakeholder engagement, adaptive management, and interdisciplinary collaboration, enabling proactive integration of FRM into development processes. This novel approach aligns flood resilience with broader urban sustainability and planning objectives, offering a practical tool for policymakers, project managers, and urban planners. Future research should focus on empirical validation and contextual adaptation of the framework across diverse socio-economic and geographical settings to enhance its global applicability.